PERILAKU PACARAN DAN MOTIVASI BELAJAR SISWA SMKF IKASARI PEKANBARU - Ulantari, Sesri; Yakub, Elni; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : At the present time dating behavior a lot of bad effects for students such as not concentrating when learning, being closed and do not want to be so that the process of student self-development hampered. The purpose this is study : 1) description of student dating behavior 2) To know the description of student learning motivation in dating. The method used is descriptive with quantitative approach. Population in this research is student of class X.1-X-6 Pharmacy dating as much as 73 student, by using technique of saturated sampling. Data collection using questionnaires and using guttman scale. The results showed that; 1) The reason for the students dating for entertainment, 2) The dating disadvantage according to the respondent is full of problems, 3) while in terms of dating benefits is the development of patterns of student interaction, 4) For the dating place students do it at school and 5) Activities performed chatting, 6) The description of students' motivation in dating in terms of instrnsik existence of encouragement and needs while extrinsic students that is the existence of a safe and conducive environment. It can be concluded that student dating behavior is at a moderate level. It is expected that bk teachers should be able to control and respond quickly in preventing and overcoming student dating behavior.Keywords : Dating Behavior, Motivation Learn